Introduction to Special Relativity - Resnick, Robert (New Delhi: Wiley India, 2005)
This book gives an excellent introduction to the theory of special relativity. Professor Resnick presents a fundamental and unified development of the subject with unusually clear discussions of the aspects that usually trouble beginners. He includes, for example, a section on the common sense of relativity. His presentation is lively and interspersed with historical, philosophical and special topics (such as the twin paradox) that will arouse and hold the reader's interest. You'll find many unique features that help you grasp the material, such as worked-out examples, summary tables, thought questions and a wealth of excellent problems.
Index 223-226p.; Reprint 2014
Keywords: Doppler effect; Forces between moving charges; Newtonian relativity; Relativistic momentum; Galilean transformations